Perancangan Aplikasi Web Profil Pada Organisasi HIPMA – LANI Tangerang Dengan Metode Waterfall - Wenda, Akianus; Firmansyah , Bagus; Putra Priyanto, Vially; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
In this digital era, organizations need an integrated platform to disseminate information widely and professionally. This study investigates the use of the Waterfall method to design a profile web application for the HIPMA-LANI Korwil Tangerang organization, which includes the stages of needs analysis, design, implementation, and system testing. This application aims to overcome the obstacles in disseminating information through social media, which has been limited and unstructured. This application can increase the accessibility of information and involvement of members and the general public with features such as contacts, galleries, articles, and main pages. The test results show that the app is effective in strengthening the organization's identity in the digital era. Further development is recommended to include dynamic features, responsive design, and interactive components for better data management.